Leveraging digital transformation in hybrid workplaces: current landscape, underlying challenges, and future prospects - Han, Yu; Wang, Xiaohui; Bai, Yuqi (Frontiers in Human Dynamics, 2025)
PurposeThis review article discusses the challenges and opportunities of digital transformation in the dynamics of innovation in hybrid workplaces. Its objectives include reviewing the literature on digital transformation, defining the challenges and drivers of innovation and providing guidance on how to optimize organizational interactions and diversity within technology-enabled working arrangements.MethodsThis study adopts a systematic literature review approach to review the theoretical frameworks of digital transformation in management, hybrid work models, and cases. Technological, cultural, and organizational enablers and constraints are discussed, and success factors for innovation in ambidextrous organizations are highlighted.FindingsThis study identifies three key enablers of innovation in hybrid workplaces, including effective communication platforms, adaptive leadership and a culture of adaptability. Conversely, barriers include resistance to change, gaps in digital literacy and challenges to inclusivity. Strategic investments in technology, employee training, and cross-functional collaboration have emerged as key recommendations for organizations to achieve digital transformation.OriginalityThis results addresses the literature gap by synthesizing knowledge on digital transformation with the effects of implementing a hybrid workplace. The suggested conceptual model focuses on practical recommendations for promoting innovation with reference to the technological and cultural challenges in today’s workplaces.ImplicationsThis study focuses on hybrid work patterns that may restrict their applicability in other work organizations, suggesting the need of further research in the direction of digital transformation’s long-term effects on innovation. This study also provides practical managerial implications that outline possible directions for establishing effective hybrid work environments for organizations by investing in technology, leadership, and employees.